2014
DOI: 10.1891/2156-5287.4.4.219
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ Time and Presence: A Key Factor in Facilitating Breastfeeding Support for New Mothers

Abstract: BACKGROUND: There is now a plethora of work that has examined new mothers’ experiences of receiving breastfeeding support. However, there remains limited literature describing women’s experiences of receiving this support from midwives in the early postnatal period.AIM: The study aimed to explore and describe women’s experiences of receiving breastfeeding support from midwives in the early postnatal period.METHOD: A qualitative descriptive approach was used. Six first-time mothers who initiated breastfeeding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…If providers experience under-resourcing they make decisions about care priorities and breastfeeding support is not prioritised. These findings support the work of other studies linking understaffing and lack of time with lack of breastfeeding support provision [75,79,80] and women's perceptions that providers are unable to provide breastfeeding support due to a lack of time and resources within healthcare organisations [75,77]. Funding cuts to breastfeeding support services are therefore not only detrimental to women's breastfeeding experiences [81] but also detrimental to provider development.…”
Section: Plos Onesupporting
confidence: 82%
See 1 more Smart Citation
“…If providers experience under-resourcing they make decisions about care priorities and breastfeeding support is not prioritised. These findings support the work of other studies linking understaffing and lack of time with lack of breastfeeding support provision [75,79,80] and women's perceptions that providers are unable to provide breastfeeding support due to a lack of time and resources within healthcare organisations [75,77]. Funding cuts to breastfeeding support services are therefore not only detrimental to women's breastfeeding experiences [81] but also detrimental to provider development.…”
Section: Plos Onesupporting
confidence: 82%
“…Full implementation and funding of evidence-based breastfeeding support interventions is imperative for providers to experience services that value breastfeeding. Consistent with the literature, participants from studies included in this review reported that working under organisational constraints, especially time pressures, impedes practice [75][76][77]. The experience of providing support in well-funded services with adequate providers available enables provision of meaningful breastfeeding support because time, training and informal learning opportunities are available.…”
Section: Plos Onementioning
confidence: 88%
“…However, current care models present barriers that contribute to perceptions and realities of midwives' lack of time, probably as a result of caseloads. 109,110 All the same, this support could begin in the prenatal period and may greatly influence a first-time mother's decisions on breastfeeding. 87 The evidence suggests that midwives and other health professionals are better equipped to provide information and practical support to first-time mothers and their families.…”
Section: Coping Through Social Mediamentioning
confidence: 99%
“…16,17 The presence of midwives is an important factor in the successful implementation of EIB. 18 The provision of midwife support to pregnant women was found to increase the success of EIB implementation by 17.5 times. 19 The first hour after birth is crucial for midwives to perform EIB.…”
Section: Introductionmentioning
confidence: 99%